Experiencing mobbing at workplace facing psychological gender and occupational burnout - Góralewska-Słońska Anna (Management)
The problem of mobbing in the work environment is significant, there are many factors determining mobbing, and its negative effects affect both the employees of the organization and their social environment as well as the work process. The aim of this study is to determine the relationship of experiencing mobbing with psychological gender dimensions and occupational burnout. 180 people participated in the study, a group of respondents consisted of 123 women and 57 men, aged 20 to 57 years. The research process used: Negative Action Questionnaire (NAQ), Psychological Gender Inventory (IPP) and Questionnaire to study behaviours and experiences related to work (AVEM).